Questioning genetically modified maize: a case of public debate in the Southern African media (1997-2007) - Mwale, Pascal Newbourne (My University, 2012)
The thesis investigates a particular public communication practice in a particular region and time. It addresses the question of the shape of public debate as a genre of public deliberation, in particular what public debate on science looks like in the media in Southern Africa. It uses texts: print news media texts that deal with debate centred on GM maize, in four Southern African countries, Zambia, Malawi, Zimbabwe and South Africa, from 1997 to 2007. The Southern African debate is region-specific and has three key drivers, the region’s underdevelopment, the centrality of maize to the region’s economies, and the inhospitability of science to the political in the region’s democratic public spheres. Coverage manifests massive slippage in the communication exchanges; it also manifests moments of engagement as in argumentative debate and the energy and vitality of the political, whose combined effect is the obscuring of the slippage. It is not a classical debate. The regional debate displays what the thesis terms ‘babelisation,’ implying at least three things: rhetorical moves –reframing, sidestepping, telescoping, and silencing; the resulting slippage; and moments of engagement as well as the energy and vitality of the political. The rhetorical moves and the slippage constitute the core of the babelisation inasmuch as moments of engagement and the energy and vitality of the political render the Babel florid and complex. The thesis argues that babelisation is a particular rhetorical feature of the regional debate.at least three of such. First, the media have an apparent handicap in how they handle debate. In the classical public sphere, the media have a double imperative of playing agent of public opinion, highlighting and playing conflict fairly and in a balanced manner. Fairness and balance in representation entail factual and impartial journalism, eschewing bias, framing, sensationalism and hype, all of which raise the spectre of the double bind. This entails that the media’s provision of space for conflict in debate to play out is considered inadequate in journalistic practice. Anything less than active mediation implies relay mediation, leading to babelisation. Yet, at the heart of journalistic practice, there is a contradiction about such a role. The contradiction is this: journalists are expected to check on active mediation; active mediation must not be seen to be ‘overactive’. Importantly, due to resource-poverty in the region’s media institutions, journalists resort to relay-mediating issues in debate arising from science, leading to babelisation. In this study, the double imperative turns into a double bind for the media. Second, the inhospitability of science to the political makes it difficult to bring the political into an area where the issues seem to be scientific and as a result of it, the protagonists and antagonists in the coverage make communication manoeuvres. It appears that this particular play out of coverage has a specific purchase in this region in particular because it enables the entry of political concerns into the same field as science, where science tends to try to seal off the political as interfering in its business, portraying politics as an extra-field activity. Babelisation enables the political to force its way into and fire up an apparent scientific controversy. Third, the Johannesburg Earth Summit provides a global deliberative forum for the interplay and interpenetration of discourses, precipitating the regional debate, resulting from the upsurge of the political. It transpires in this study that, babelisation allows the political to enter into an area of deliberation where, otherwise, science is ring-fenced. Babelisation allows for colonial and apartheid legacy anxieties and related issues to find media space, gaining sustained visibility and audibility. Finally and yet importantly, babelisation allows for a wider deliberative space, thereby constituting a potentially all-inclusive democracy. Hitherto, theorists of journalism and media studies, the public sphere, and deliberative democracy have not imagined this communication phenomenon. Therefore, the concept of babelisation speaks distindistinctively to the particular concerns of our particular time in this particular region of Africa. The thesis then proceeds to explore conditions of babelisation and it identifies
Ph.D. University of South Africa, Faculty of Humanities, 2012